The Development of Various Speech Components and Their Relations with the State of the Brain Executive Functions in Senior Preschool Age - Zakharova, M. N.; Agris, A. R. (Human physiology, 2023)
The brain executive functions (EFs) are crucial for various aspects of child development, as they stipulate control of cognitive processes and behavior. Speech development is one of the most important goals of preschool age and a defining predictor of successful school education. Both classical and contemporary studies emphasize relations between these functions. In order to achieve an in-depth comprehension of the relations we have deepened a comparative neuropsychological research by means of complemented speech function assessment (phonological process, verbal memory, motor program sequencing, grammatical and lexical speech design, planning of utterance) and conducted it targeting children aged 5–6 ( n = 61, average age 5.67 ± 0.33 years) and 6–7 ( n = 117, average age 6.67 ± 0.29 years) years. The research has revealed age-specific differences of the given age groups (verbal memory ( р ≤ 0.002), comprehension of logical grammatical constructions ( р < 0.001), lexical ( р = 0.031) and grammatical ( р = 0.008) speech design, and planning of utterance ( р < 0.001)). The coherence of speech and the state of EF development increases in the age from 5–6 to 6–7 years and is evident in various aspects of coherent speech (planning of utterance and its grammatical and, to a lesser degree, lexical speech design), verbal memory, and verbal logical thinking; in phonological processing, motor program sequencing, and comprehension of logical grammatical constructions, however, it is less evident as it is related to particular indexes, but still exists. The research findings can be used to further voluntary regulated speech development and correction programs targeting senior preschoolers, as well as to develop voluntary regulation and control incorporating various speech components.